Reformulation of the Indonesian National Police Code of Ethics as an Effort to Eliminate Normative Ambiguity in Handling Horizontal Conflicts Involving Police Officers - Sonny Wibisono; Riswadi Riswadi (Greenation Research & Yayasan Global Resarch National, 2025)
Reformulation of the National Police Code of Ethics is an urgent need to address the various dynamics of horizontal conflict management involving police officers. Ambiguities in ethical norms as stipulated in the Republic of Indonesia National Police Regulation Number 7 of 2022 create difficulties in interpretation and implementation in the field. It results in unclear actions by officers in social crises, which have the potential to lead to ethical and human rights violations. This study uses a normative juridical approach to analyze relevant laws and regulations, namely Law Number 2 of 2002 concerning the Republic of Indonesia National Police, Government Regulation Number 2 of 2003 concerning Disciplinary Regulations for National Police Members, and Regulation No. 7 of 2022 concerning the Professional Code of Ethics and the National Police Code of Ethics Commission. The analysis reveal that several articles in Regulation No. 7 of 2022 contain norms that are open to multiple interpretations, do not accommodate the complexity of horizontal conflict situations, and lack contextual elaboration instruments. This study recommends reformulating the code of ethics by prioritizing the principles of lex certa and lex stricta, and suggesting harmonization of internal Polri regulations. Furthermore, strengthening the Polri Code of Ethics Commission is needed to ensure that ethical norms are enforced objectively, accountably, and in line with human rights values. This reformulation is expected to provide a clear ethical direction for Polri personnel and strengthen public trust in the police institution in handling social conflicts.